Factors Influencing Precision Agriculture Technology Adoption Among Small-Scale Farmers in Kentucky and Their Implications for Policy and Practice - Shreesha Pandeya; Buddhi R. Gyawali; Suraj Upadhaya (Agriculture)
The increasing pressure on food security and environmental sustainability has emphasized the importance of effective farm resource usage. Precision agriculture technologies (PATs) have been considered as one of the solutions to these challenges. Multiple stakeholders and agencies working in the agriculture sector have implemented various initiatives to facilitate their adoption. Despite numerous initiatives, the adoption of PATs in small farms is shallow in the United States. It is important to understand what socio-economic and demographic factors influence their decision-making regarding PAT adoption. This research aimed to provide actionable insights that can help farmers overcome existing challenges and capitalize on the benefits of advanced agricultural practices, ultimately contributing to the resilience and sustainability of the agricultural sector. This study used a mixed approach (a combination of mail, in-person, and focus group discussion) to investigate factors influencing PAT adoption by small-scale farmers in Kentucky. The data were analyzed using the binary logistic regression method. The results revealed that farm size and longer years of farming experience increased the likelihood of PAT adoption, whereas farmers’ age negatively affected adoption. Other demographic variables, such as gender, income, and education, did not influence adoption significantly. To promote the adoption of PATs among small farmers in Kentucky, policies should focus on supporting younger farmers and building PATs suitable for operating in small farms and reducing barriers. Furthermore, providing targeted training and resources to small-scale farmers can help to promote the adoption of these technologies, thereby improving agricultural efficiency and sustainability.